Evaluation of Quality Management Implementation Using the Process Hierarchy Analysis Method - Prasetyo, Agus Budhy; Sembiring, Desiran; Murtiadi, Suryawan (ASTONJADRO, 2026)
The construction project of the Soekarno-Hatta Airport Police Headquarters represents a strategic step in enhancing security infrastructure and public services within the international airport area. This study aims to analyze the implementation of project quality management based on ISO 9001:2015 and the principles of Total Quality Management (TQM). The Analytical Hierarchy Process (AHP) method was employed to determine the priority of quality criteria in a structured manner through pairwise comparison questionnaires administered to project experts. the analysis results indicate that continuous improvement is the most dominant factor (13.16%), followed by occupational health and safety implementation (11.82%) and project management leadership (11.70%). other factors include personnel involvement (11.36%), evidence-based decision making (10.85%), customer focus (10.79%), product and service control (10.29%), risk and opportunity management (10.02%), and process approach (10.00%). these findings underscore that the synergy between leadership, quality culture, occupational safety, and risk management influences the success of construction projects. the integration of iso 9001:2015 and tqm serves not only as a quality control mechanism but also as a strategy for enhancing project and sustainability.